Micropolar fluid flow through a stenosed bifurcated artery - Srinivasacharya, Darbhasayanam; Rao, Gade Madhava Madhava (Nonlinear Analysis: Modelling and Control, 2017)
The aim of this article is to investigate the blood flow in bifurcated artery with mild stenosis taking blood as a micropolar fluid. The arteries, forming bifurcation are taken to be symmetric and straight cylinders of finite length. The governing equations are non-dimensionalized and coordinate transformation is used to convert the irregular boundary to a regular boundary. The resulting system of equations is solved numerically using the finite difference method. The variation of velocity, microrotation, shear stress, flow rate and impedance near the flow divider with relevant physical parameters are presented graphically. It is found that, due to backflow and secondary flow, impedance and flow rate are perturbed largely at the apex. It is also seen that the microrotation changes it's sign from negative to positive for increase values of bifurcated angle and micropolar coupling number.
Keywords: micropolar fluid; bifurcated artery; stenosis; shear stress; impedance